THE EFFECT OF INFORMATION TECHNOLOGIES ON EMPLOYEES - (:unkn) unknown (LOOKUS SCIENTIFIC, 2013)
Until now the existence of human beings can survive a continuous struggle for change and adaptation within the indispensability of dizzying. Prior to the 20th century and the industrial evolution of the dizzying speed of change and transformation, then the evolution of information technology has become the most densely inhabited century. In retrospect, since the existence of mankind in the last century was the most radical transformations. Variable is the change in societies such as businesses have become indispensable. Knowledge is more important than the effect of competition in order to get a part of cake of the world. Competitiveness of enterprises, which is part of modern life and modern business approach naturally, requires the integration of modern technologies. Technological evolution in the last stage of the relative knowledge is the main theme of the concept of development. Understanding of the development of information technologies underlying today's most important requirement in this context. In this study, Generally the number of computers, functions of information technology, information system that uses the number of personnel, Information System, the annual investment amount, the existence of support services unit, using special software, software development units, the presence of the amount of access to the internet, intranet and extranet use, office automation systems use of electronic data interchange systems, IT strategic planning, what kind of interactions between features and functions that employee satisfaction will be examined.
Keywords: Information; Information Systems; Information Technology; Intranet; Extranet; JOB-SATISFACTION; WORK; MOTIVATION